Nutritional Values and Functional Properties of House Cricket (Acheta domesticus) and Field Cricket (Gryllus bimaculatus) - Udomsil, Natteewan; Imsoonthornruksa, Sumeth; Gosalawit, Chotika; Ketudat-Cairns, Mariena (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2019)
The used of insects as protein sources is growing rapidly for a variety of reasons, including global food security, sustainability, nutritional value and animal welfare. The nutritional composition and functional properties of extracted proteins from two cricket species (A. domesticus and G. bimaculatus) were investigated. Both cricket species contained high amounts of proteins (60–70% dry weight) with all essential amino acids and 10–23% lipids. The amount of omega-3 and omega-6 fatty acids and several minerals, such as P, Na and Ca were also high. Proteins were isolated from both cricket species by solubilisation at pH 11.0–12.0, followed by pH 4.0 isoelectric precipitation. The cricket proteins have high water capacity, moderate foaming capacity and stability with high emulsion activity. Therefore, they certainly could be further utilized as ingredients in various food types that could be an alternative nutritional source for both direct consumption and processing for protein extracts.